PERBEDAAN EFEKTIFITAS BURPEE INTERVAL TRAINING DENGAN LATIHAN AEROBIK INTENSITAS RINGAN DALAM PENURUNAN KOMPOSISI TUBUH MAHASISWA OVERWEIGHT - Komang Dhyanayuda P.; Ni Luh Nopi Andayani; Putu Adiartha Griadhi; I Wayan Sugiritama (Majalah Ilmiah Fisioterapi Indonesia, 2016)
ABSTRACTThe research was to determine difference in the effectiveness between burpee interval training and low intensity aerobic to decrease body composition consist of weight, BMI, fat percentage, and BMR in overweight students. This research design is an experiment with randomize pre-test and post-test control group design. These samples are 14 people who were divided into two groups, burpee interval training and low intensity aerobic group. After the research data was complete, The data analyzed was using paired sample t-test and Wilcoxon match pair test, in the burpeegroup showed each p=0.061;0.068;0.079;0.068 with mean (1.3±0.9;-20.6±24.2;2.65±2;-116.2±24.2). In aerobic group showed p=0.448;0.18;0.098;0.655 with mean (0.5±0.6;1.6;1.9;2.25±0.49;3±39.5). Furthermore, test the hypothesis using independent samples t-test to determine different test between burpee and aerobic group was done by independent sample t-test and obtained each p =0.813;0.909;0.807; 0.009. Keywords: Body Composition, Burpee Interval Training, Low Intensity Aerobic